2018
DOI: 10.1172/jci.insight.97076
|View full text |Cite
|
Sign up to set email alerts
|

Retinal de novo lipogenesis coordinates neurotrophic signaling to maintain vision

Abstract: Membrane lipid composition is central to the highly specialized functions of neurological tissues. In the retina, abnormal lipid metabolism causes severe forms of blindness, often through poorly understood neuronal cell death. Here, we demonstrate that deleting the de novo lipogenic enzyme fatty acid synthase (FAS) from the neural retina, but not the vascular retina, results in progressive neurodegeneration and blindness with a temporal pattern resembling rodent models of retinitis pigmentosa. Blindness was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 57 publications
1
22
0
Order By: Relevance
“…Moreover, using postmortem human retina samples, we recently obtained data suggesting alterations in lipid metabolism in retinas from donors with diabetic retinopathy (P. E. Fort, unpublished data), consistent with the reduction observed in BKS db/db mice [30]. The importance of these findings is highlighted by the observation that genetic deletion of the fatty acid synthase gene in the neuroretina leads to progressive neurodegeneration, with synaptic dysfunction, neuronal cell apoptosis and visual impairment [64]. As these pathological changes are also observed in diabetic retinopathy, the possibility arises that impaired lipid synthesis may contribute to the neurodegenerative effects of diabetes on the retina.…”
Section: Rise Of the Role Of Lipid Metabolism In Diabetic Complicationssupporting
confidence: 72%
“…Moreover, using postmortem human retina samples, we recently obtained data suggesting alterations in lipid metabolism in retinas from donors with diabetic retinopathy (P. E. Fort, unpublished data), consistent with the reduction observed in BKS db/db mice [30]. The importance of these findings is highlighted by the observation that genetic deletion of the fatty acid synthase gene in the neuroretina leads to progressive neurodegeneration, with synaptic dysfunction, neuronal cell apoptosis and visual impairment [64]. As these pathological changes are also observed in diabetic retinopathy, the possibility arises that impaired lipid synthesis may contribute to the neurodegenerative effects of diabetes on the retina.…”
Section: Rise Of the Role Of Lipid Metabolism In Diabetic Complicationssupporting
confidence: 72%
“…FAS catalyzes the committed step in de novo lipogenesis 18 and is highly expressed in neural tissue and important for neurogenesis 19 . A recent study showed that deletion of FAS from the neural retina resulted in progressive neurodegeneration and blindness, mimicking an animal model for retinitis pigmenotsa 20 . We 4 and others 14 , 21 have shown PKM2 to be a transcriptional co-activator in gene regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of FASN in the neural retina has been shown to result in progressive neurodegeneration resembling RP in mouse models [22]. Additionally, we have previously shown that metabolic and antioxidant stress proteins were regionally expressed within the human retina, in particular the OXPHOS and TCA cycle pathways, indicating that the retinal neural network is likely sensitive to changes within the metabolic pathways that occur during disease [13].…”
Section: Oxidative Metabolic Pathways Are Downregulated In the Pde6ɑ mentioning
confidence: 91%
“…Glucose metabolism also feeds into fatty acid synthesis and lipid metabolism pathways, which are responsible for maintaining proper membrane lipid composition in neuronal cells [21]. Disruption of lipogenesis (by deleting fatty acid synthase) in the neural retina leads to abnormal synaptic structure and apoptosis, resulting in a phenotype resembling RP [22]. Thus, loss of these key metabolic pathways and enzymes would result in abnormal nutrient and metabolite availability, and impaired visual function.…”
Section: Introductionmentioning
confidence: 99%